P41 MELDNa as a predictor of 6-week mortality for patients presenting with portal-hypertensive bleeding precipitating acute cirrhosis decompensation. (20th September 2022) - Phillips, Alexandra; Gananandan, Kohilan; Chikhlia, Anmol; Old, Hannah; Sim, Sharmaine; Hussain, Ishrat; Kazankov, Konstantin; Mookerjee, Rajeshwar
Abstract : Introduction: The management of variceal bleeding has significantly evolved over the last 3 decades with improvements in portal hypertension management, early emergency endoscopy-access, and intensive care. Despite these changes, significant morbidity and mortality remain. This observational study assessed the characteristics, management, and outcomes for portal hypertension-related bleeding in a London, tertiary bleeding-referral centre. Methods: A retrospective evaluation of decompensated cirrhosis admissions to Royal Free London, October'18-February'21. Patients were included if they had an admission with acute cirrhosis decompensation (defined: new onset/increasing jaundice or ascites; infection, encephalopathy, portal-hypertensive bleeding or renal dysfunction). Admissions were excluded if they lasted < 24 hours, were elective or occurred post liver-transplant. Information regarding gastrointestinal bleeding was obtained from the endoscopy reporting tool (Unisoft-medical-systems; London). Results: 390 patients were admitted to hospital with decompensated cirrhosis with a total of 591 admissions. 315 endoscopies were performed in total with bleeding listed as the indication for 202 endoscopies (64.1%), and 127 (62.9%) of those were found to have varices. The overall 6-week mortality for those with portal hypertension and a decompensation indication as bleeding, was 20%, with a rebleed rate of 14.6%. The Receiver Operator Characteristic (ROC) curve using MELDNa on admission to predict 6-week mortality produced an area-under-the-curve (AUC) of 0.835. A cut-off MELDNa>20 selected with a sensitivity of 0.83 and specificity of 0.74, demonstrated significantly higher mortality for these patients compared to those with MELD<20 [45.5% vs 5.7%, p<0.001; OR 13.9 (CI 3.6–53.7)]. These findings are illustrated in the Kaplan Meier, figure 1, censored at 42 days. Of the 86 patients who underwent an endoscopy for bleeding and found to have varices, 25 (29.1%) were transferred for tertiary management. The 6-week mortality was significantly higher in transferred patients compared to local admissions (36% vs 14.8% p=0.028), despite having comparable mean MELDNa scores on admission (18.8 vs 17.0 p=0.806). Discussion: MELDNa > 20 can be used to predict 6-week mortality in patients with gastrointestinal bleeding and varices. Our data suggests a higher mortality than has been historically reported, despite advances in care and tertiary level management. Given that mortality was significantly higher in transferred patients, suggests a need for early referrals and dialogue with tertiary centers, to improve outcomes.